ANALISIS SEBARAN FASIES DISCRETE ROCK TYPE (DRT), LAPISAN BASAL SAND DENGAN METODE ROCK TYPING PADA LAPANGAN MINYAK JULIE, CEKUNGAN ASRI, SUMATRA TENGGARA - Julie Juwita Nahari (Program Studi Teknik Geologi, Fakultas Teknik, Universitas Diponegoro, 2013)
Julie Oil Field is located in the Asri Basin, Southeast Sumatra, Indonesia. The main reservoir hydrocarbon target mostly in upper part Zelda Member of Talang Akar Formation with the thickness of the layer about 53 ft, but there is a potential hydrocarbon reservoir characteristics in lower part Zelda Member of Talang Akar Formation represented by basal sand layer with the maximum thickness 26 ft. Basal sand layer is dominated of sandstone with fragments derived from igneous rock basement (granodiorite) of this basin.This study purpose to determine the distribution of Discrete Rock Type (DRT) Facies, basal sand layer are classified based on the value of DRT to facies sedimentation, which is obtained using the method of Rock Typing (Amaefule et al, 1993). The data that used for this study are wireline log, core, and seismic interpretation.Rock Typing a quantitative method of rock classification into multiple units using its petrophysical properties such as porosity, permeability and clay volume, parameter of this petrophysical properties will be used to determine the value of Reservoir Quality Index (RQI) which is equal to 0.0314√(k/????), Normalized Porosity Index (????z) which is equal to ????/(1-????), then get the value of Flow Zone Unit (FZI) which is equal to RQI/????, so that it can be determined the classification of rock as Discrete Rock Type (DRT). Based on grouping of the data on the curves cross plot between ????z VS RQI, obtained 5 grouping rock types (DRT) there are DRT 0 (FZI = <0.0508 µm), DRT 1 (FZI = 0509-1073 µm), DRT 2 (FZI = 1,156 - 1,610 µm), DRT 3 (FZI = 1.62 - 3.96 µm) and DRT 4 (FZI => 0.9 µm). Basal sand layer deposite on terrestrial depositional environment braided river system, with facies sedimentation of floodplain facies, main channel facies and channel bar facies, with direction of sedimentation trending Southeast and distribution of depositional DRT Facies trending Southwest-Northeast.